Job loss disrupts individuals’ mobility and their exploratory patterns - Simone Centellegher; Marco De Nadai; Marco Tonin; Bruno Lepri; Lorenzo Lucchini (iScience, 2025)
Summary: In recent years, human mobility research has discovered universal patterns capable of describing how people move. These regularities have been shown to partly depend on individual and environmental characteristics (e.g., gender, rural/urban, and country). In this work, we show that life-course events, such as job loss, can disrupt individual mobility patterns. Adversely affecting individuals’ well-being and potentially increasing the risk of social and economic inequalities, we show that job loss drives a significant change in the exploratory behavior of individuals with changes that intensify over time since the job loss. Our findings shed light on the dynamics of employment-related behavior at scale, providing a deeper understanding of key components in human mobility regularities. These drivers can facilitate targeted social interventions to support the most vulnerable populations.